2019
DOI: 10.3345/kjp.2018.07276
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on partially hydrolyzed protein infant formula in nonexclusively breastfed infants

Abstract: The World Health Organization recommends that infants should be exclusively breastfed for the first 6 months of life to provide optimal nutrition in this critical period of life. After this, infants should receive nutritionally adequate and safe complementary foods while breastfeeding continues for up to 2 years of age or beyond. For nonbreastfed infants, infant formula is an available option to provide the nutrition needed. Infant formula is usually prepared from industrially modified cow’s milk and processed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
1
22
0
5
Order By: Relevance
“…However, half of the infants with allergy or atopic dermatitis in the first year of life had no prior family history of allergy; the use of PHw formulas in the general infant population has also proven to be efficacious in reducing the risk of developing atopic dermatitis 27 . In recent years, the metabolic response to partially hydrolyzed infant formula has been questioned based on the assumption that PHw formulas would result in a higher postprandial aminoacidemia and thus, greater insulin secretion by the pancreatic β-cells 28 , due to the fact that PHw protein induces more rapid gastric emptying and a higher release of plasma amino acids compared with intact protein 29,30 . Moreover, a 2016 consensus statement concluded that there was a lack of data related to the metabolic effects of PHw formulas 6 .…”
Section: Discussionmentioning
confidence: 99%
“…However, half of the infants with allergy or atopic dermatitis in the first year of life had no prior family history of allergy; the use of PHw formulas in the general infant population has also proven to be efficacious in reducing the risk of developing atopic dermatitis 27 . In recent years, the metabolic response to partially hydrolyzed infant formula has been questioned based on the assumption that PHw formulas would result in a higher postprandial aminoacidemia and thus, greater insulin secretion by the pancreatic β-cells 28 , due to the fact that PHw protein induces more rapid gastric emptying and a higher release of plasma amino acids compared with intact protein 29,30 . Moreover, a 2016 consensus statement concluded that there was a lack of data related to the metabolic effects of PHw formulas 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies have shown that the role of nutrition intervention could also play in gut microbiota production for unbreastfed babies. 41,42 Some clinical and preclinical studies demonstrate that synbiotics can prevent certain allergic diseases. This contributed to the use of synbiotic to compensate for early microbial bowel disruptions.…”
Section: Nutrition Intervention To Reduce Risk Of Developing Allergymentioning
confidence: 99%
“…Historical research regarding protein source in formula has primarily focused on soy vs. dairy-based formula [ 2 , 3 , 4 ], and an extensive focus on the degree of protein hydrolysis as it relates to immune-related conditions, such as eczema and type 1 diabetes [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Limited work has focused on growth and shown that both partially and fully hydrolyzed protein sources do result in reduced growth rates (compared to intact protein formula), more similar to breastfed infants [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%